Spinal Cord Injury With Tetraplegia in Young Persons After Diving Into Shallow Water: What Has Changed in the Past 10 to 15 Years?. Issue 8 (October 2021) - Ull, Christopher; Yilmaz, Emre; Jansen, Oliver; Lotzien, Sebastian; Schildhauer, Thomas A.; Aach, Mirko; Königshausen, Matthias
Study Design: Retrospective, monocentric, observational study in a tertiary health care center. Objectives: To analyze prehospital and clinical findings, complications, neurological improvement and follow-up in a young person cohort with spinal cord injury (SCI) and tetraplegia according to the American Spinal Injury Association (ASIA) Impairment Scale (AIS) A to D after diving into shallow water. Methods: Included were all persons younger than 50 years with SCI after head-first diving into shallow water between June 2001 and June 2019. All persons with SCI were divided into complete tetraplegia (AIS A) and incomplete tetraplegia (AIS B, C, and D) to test differences. Results: A total of 59 males (98.7%) and 1 female with a mean age of 27.7 years suffered an SCI. Alcohol use was documented in 25 cases (41.7%). At the time of admission, 33 people (55%) showed a complete tetraplegia (AIS A) and 27 showed an incomplete tetraplegia with 8 AIS B (13.3%), 15 AIS C (25%), and 4 AIS D (6.7%). At the time of discharge, people with initially complete tetraplegia showed a significant improvement from admission to discharge ( P ≤ .004). Persons with incomplete tetraplegia were more likely to improve their neurological status compared with complete tetraplegia patients ( P ≤ .001). Especially persons with complete tetraplegia suffered from typical SCI-related problems and complications. Conclusions: People with SCI and tetraplegia at the time admission show neurological improvement in 50% of the cases with an overall better outcome in persons with incomplete tetraplegia. The surgical treatment of SCI within 24 hours seems to be associated with a better neurological outcome and a lower level of tetraplegia. The incidence of SCI caused by diving into shallow water remains stable without a significant change, especially in high-risk groups. More education and prevention programs are necessary to avoid these injuries.